Ministerial decree No. 235/2013 regarding some commodities required to be paid in full price denominated in foreign convertible currencies upon exporting thereof / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Ministry of Industry and foreign Trade Decree No. 235 for the Year 2013 – List of the commodities that are required to be paid for in full via one of the banks operating within the Arab Republic of Egypt upon exporting thereof وزارة الصناعة والتجارة الخارجية قرار رقم 235 لسنة 2013 – قائمة السلع التى يشترط عند تصديرها سداد كامل قيتها عن طريق أحد البنوك العاملة داخل جمهورية مصر العربية